Stress orientation dependence for the propagation of stacking faults and superlattice stacking faults in nickel-based superalloys. (15th October 2020) - León-Cázares, F.D.; Monni, F.; Rae, C.M.F.
Graphical abstract: Abstract: Superlattice stacking fault propagation dominates the creep deformation behaviour of nickel-based superalloys at intermediate temperatures. These planar defects may appear under many different configurations depending on the dislocation arrangements and their interactions with the precipitates. Whilst these have been spotted and described before, no systematic way to explain their configurations has been provided. The current study quantifies the types of faults in multiple grains within a tensile crept polycrystalline alloy via a combination of scanning transmission electron microscopy and electron backscatter diffraction. A new defect consisting of a superlattice intrinsic stacking fault in the precipitates and an extrinsic stacking fault in the matrix is observed and a mechanism for its formation is proposed. In combination with data from the literature on single crystals, the results are incorporated into a robust framework to discern the orientation dependencies of these faults. A comprehensive analytical model based on a series of one-dimensional force balances on different dislocation configurations is developed first for the case of athermal stacking fault propagation for the cases of cuboidal and spherical precipitates. The model is then extended to include six configurations of superlattice faults and microtwinning. This results in novel mechanistic maps that account for stress, orientation and microstructure, with excellent qualitative agreement with experiments.